Ecological Themes in Human-Nature Relationships: An Ecocritical Analysis of Bukidnon’s Gugud - Dorias, Vincent Jhun (International Journal of Language and Literary Studies, 2024)
This study aims to identify the human-nature relationships, examine how ecological concerns are articulated, and deduce the key ecological themes in the six gugud of the Indigenous communities in Bukidnon, Philippines. Gugud, a traditional form of storytelling, encapsulates narratives of the Indigenous communities, highlighting unique and diverse knowledge of their relationship with the environment. By utilizing ecocriticism as a literature approach and guided by the concepts of human-nature relationships by Nan-sheng & Guangwu as cited by Tang et al. (1989), data from the gugud shows three dominant relationships: humanized nature, set-foot nature, and man-made nature. Moreover, these relationships from the Bukidnon indigenous communities also gleaned three ecocritical themes: humans as superior, will always be part, and coexistent yet adversarial to nature. The elucidated themes highlight the heightened need for humanity to adopt sustainable approaches to the utilization and stewardship of natural resources, urging consciousness and responsibility toward the environment that can ensure the mitigation of ecological destruction and the sustainability of the planet for future generations. This study asserts that Bukidnon, like other Indigenous communities worldwide, views folk literature not just as a cultural artifact, but as a lens that reveals the interconnectedness between humans and the environment.